99 cent solutions : save a fortune the old fashioned five-and-dime way - Bowers, Sharon. frey50; McCabe, Allison; Randol, Susan (Pleasantville, N.Y. : Reader's Digest, 2010)
Includes 1377 "live well for less" tips.
Groceries -- Health and beauty -- Gardening and outdoors -- Cleaning and home supplies -- Housewares -- Notions -- School and party supplies -- Tools -- Lunch counter legends.
"Clever uses for everyday stuff"--Cover.
"Cent" in the title is represented by a cent sign.
Includes index.
Keywords: Home economics; Finance, Personal